The Effect of Soursop Leaves Fraction (Annona squamosa L.) as Anticancer - Makbruri Amin; Irsan Saleh (HM Publisher, 2020)
Anticancer drugs are primarily aimed at inhibiting the growth and proliferation of cancer cells. The soursop plant (Annona squamosa L.) has the potential to be developed as an anticancer drug. This plant contains several active compounds including flavonoids, borneol, camphor, alkaloids, terpenes, saponins, tannins, polyphenols, and polyketide compounds. This study was conducted to assess the efficacy of the polar fraction of soursop leaves on cytotoxic activity based on the IC₅₀ value in T47D cells. This research is experimental in vitro study using cell line T47D. The methanol fraction of soursop leaves was diluted with DMSO and DMEM to obtain a concentration of 500; 250; 125; 62.5; 31.25 µg/ mL cisplatin with a concentration of 50:25:12,5: 6,25:3,125 µg/mL. The methanol fraction of soursop from the highest concentration of 500 µg/ml has average viability of 46.77% and the average percentage of viability will increase in proportion to the decrease in the concentration of the test compound. The IC50 value shows the concentration value that results in the inhibition of cell proliferation by 50% of the population. In conclusion, the methanol fraction of soursop leaves have an anticytotoxic effect on the T47D cell line through the role of flavonoid metabolites.